Formulation and evaluation of fluconazole-loaded in situ gel nanoemulsion using polymeric systems for ocular antifungal therapy - Ardeshi Emrani; Seyedeh Negin Kassaee; Pegah Changavi; Adel Salahi; Shabnam Pourmoslemi; Mohammad Mehdi Mahboobian (International Journal of Nanoscience, 2026)
The therapeutic efficiency of topical antifungal drops is limited due to rapid precorneal clearance and short residence time, which reduce drug bioavailability at the site of infection so this study aimed to develop and evaluate a thermosensitive in situ gelling nanoemulsion of fluconazole for enhanced ophthalmic delivery and prolonged ocular retention. Pseudo-ternary phase diagrams were constructed by using Triacetin as the oil, Propylene glycol as the co-surfactant, Cremophor ® RH 40 as the surfactant and water to determination of the O/W nanoemulsion region and optimize formulation composition. Six prepared fluconazole-loaded nanoemulsions were characterized by droplet size, poly disperse index (PDI), refractive index (RI), pH and viscosity. The selected formulation was developed for thermosensitive nanoemulsion by using Poloxamer 188 & 407. Optimized sample was evaluated for release, stability and antifungal activity. The optimized nanoemulsion with 5% of Triacetin, 5% Cremophor ® RH 40 and 5% Propylene glycol and 0.3% fluconazole exhibited a mean droplet size of approximately 15 nm with a PDI of 0.270, indicating a homogeneous nanosystem with a narrow size distribution. The formulation demonstrated viscosity around 3 cp and underwent a rapid sol-to-gel transition at 33.6°C, closely matching the physiological temperature of the ocular surface. In vitro release studies revealed a sustained release profile, with 59.71% of fluconazole released over 8 h. Furthermore, the formulation exhibited notable antifungal activity, producing an inhibition zone of 33 mm against the tested fungal strain. In conclusion, the optimized thermo-sensitive in situ gelling nanoemulsion demonstrated favorable physicochemical characteristics, sustained drug release, satisfactory stability, and effective antifungal activity. These findings suggest that the proposed delivery system represents a promising strategy for improving the ocular bioavailability and therapeutic efficacy of fluconazole in the treatment of fungal eye infections.